Transition-Metal-Free Selective Halocyclization of N-Alkoxy Amides: Synthesis of N-Alkoxy Lactams and Oximinolactones - Chakave, Sunil Dattatray; Hapse, Venunath; Inamke, Kishor Balkrishna; Dehade, Amol Satish; Dessai, Anupa; Montgomery, Mark; Sonawane, Ravindra Punjaji; Kandukuri, Sandeep R.; Manjunath, Bhanu N. (Synthesis, 2024)
A new method for the synthesis of N-alkoxy lactams and oximinolactones, involving the selective N-cyclization and O-cyclization of unsaturated N-alkoxy amides, is presented. This approach features mild reaction conditions and no requirement for transition-metal catalysts. The protocol demonstrates a wide range of applicability in 5-exo-trig and 6-exo-trig cyclization, accommodating chloro, bromo, and iodo electrophiles. The N-cyclization process can be achieved in the presence of strong lithium base such as LiHMDS or n-BuLi, while the O-cyclization occurs spontaneously without the addition of any base. Mechanistic studies reveal the N-cyclization reactions proceed through cyclic lithium intermediates, as confirmed by FT-IR studies and control experiments, which contribute to the N-selectivity. The current methodology was successfully used in synthesis of natural product (E/Z) des-hydroxy triticone A and B.
Keywords: halocyclization; lactams; N-alkoxy amides; oximinolactones; triticone A and B